Synthesis and Crystal Structure of 4-Formaldehyde Benzaldehyde Methylthiosemicarbazone - Su, Wei; Qian, Quanquan; He, Chunling; Liu, Lifeng; Zhou, Quan; Li, Peiyuan (Asian Journal of Chemistry, 2013)
A thiosemicarbazone single crystal synthesized with molecular formula as C10H11N3OS, was synthesized by 1,4-phthalaldehyde and 4-methylthiosemicarbazide. The crystal is monoclinic, space group P21/c with unit cell parameters: a = 10.1467(3) Å, b = 8.5255(2) Å, c = 13.1531(3) Å, a = 90.00º, b = 103.417(2)º, g = 90.00º, V =1106.75(5) Å3, Z = 4, Mr = 322.23, Dc = 1.934 g/cm3, μ = 1.682 mm-1, F(000) = 635, R = 0.0342, wR = 0.0807 for 11143 reflections with I > 2s(I).